Clinico-radiological Profile and Outcome of Children with Viral Pneumonia admitted to Paediatric Intensive Care Unit in the pre COVID 19 period - Aroor, Shrikiran; Mundkur, Suneel; Kumar, Sandeep (Journal of Nepal Paediatric Society, 2022)
Introduction: Viruses are common etiological agents of severe acute respiratory illness in under five children. Very few studies are available considering the profile of children with viral pneumonia admitted to paediatric intensive care unit (PICU) in our setting. Hence this study was done to describe the clinico- radiological profile and outcome of children diagnosed with viral pneumonia admitted to PICU. Methods: This was a retrospective descriptive study done in the PICU of a tertiary care hospital in South India. The presenting clinical features, blood parameters, chest radiography findings, course during the hospital stay and outcome of children with viral pneumonia (RT- PCR Positive) admitted to PICU were studied. Results: The aetiological profile of 28 children included - Influenza virus - 14 cases, Respiratory Syncytial Virus - 6 cases, Adeno virus - 4 cases, Human Boca virus - 2 cases, Human Rhino Virus - 1 case and Human metapneumo Virus - 1 case. Majority of children (50%) presented with severe respiratory distress. Predominant radiological picture included bilateral interstitial infiltrates followed by patchy alveolar consolidation. Eight children required mechanical ventilation. Complications included septic shock and MODS (n = 5), pneumothorax (n = 2), myocarditis (n = 2), pleural effusion (n = 1), ventilator associated pneumonia (n = 2) and pulmonary artery hypertension (n = 2). Mortality was observed in seven (25%) children. SpO2 / FiO2 ratio < 300, shock at admission, neutrophil leucocyte ratio > 2 and hypoalbuminemia were found to be significant predictors of mortality. Conclusions: Malnutrition and iron deficiency analmia were the common risk factors. Patchy alveolar consolidation is also a common radiological finding along with interstitial infiltrates. Hypoalbuminemia was a common finding among non-survivors.